Intraoperative versus postoperative rendezvous endoscopic retrograde cholangiopancreatography to treat common bile duct stones during cholecystectomy. Issue 1 (24th July 2018) - Noel, Rozh; Arnelo, Urban; Swahn, Fredrik
Abstract : Background and Aim: The rendezvous postoperative endoscopic retrograde cholangiopancreatography (ERCP) technique has been introduced as a modification of the single‐session rendezvous intraoperative ERCP procedure in the management of concurrent common bile duct stones during cholecystectomy. There are no reports on the impact of this modified technique on post‐ERCP morbidity. The objective of the present study was to study and compare the rendezvous techniques in terms of procedure‐associated morbidities, such as post‐ERCP pancreatitis and postoperative infections. Methods: The Swedish National Registry for Gallstone Disease and ERCP was searched for ERCP procedures cross‐matched with cholecystectomies for the same patient carried out for gallstone indications between 2008 and 2014. A total of 1770 rendezvous ERCP procedures were retrieved and included in this study. The ERCP procedures were considered rendezvous intraoperative or rendezvous postoperative, depending on whether the ERCP procedure was carried out during or after completing the cholecystectomy. Results: There were 1205 and 565 ERCP procedures in the rendezvous intraoperative and the rendezvous postoperative groups, respectively. The cohorts were similar in age and gender distribution. Overall complication rates were higher in the rendezvous postoperative group compared with the rendezvous intraoperative group (19.7% vs 14%, P = 0.004), involving specifically post‐ERCP pancreatitis (6.4% vs 3.2% P = 0.003) and postoperative infections (4.4% vs 2.3% P = 0.028). Despite similar stone clearance rates, there were higher rates of retained stones in the rendezvous postoperative group (5.5% vs 0.6%, P < 0.001). Conclusions: Single‐session rendezvous intraoperative ERCP is superior to the rendezvous postoperative ERCP technique in terms of post‐ERCP pancreatitis and postoperative infections.